In grace we may forget: Recollection for the sake of reconciliation in Barth and Mandela - Mark, Edwards (Stellenbosch Theological Journal, 2020)
This article defends the active role Barth gives to God's grace as humans forget and remember. Barth holds humanity's ability or inability to recollect memories, especially traumatic ones, as divinely willed for the sake of reconciliation with the past. Arguing this as consistent with Barth's broader theology of time and eternity, the article defends this as a correlation of Mandela's conviction that "True reconciliation does not consist in merely forgetting the past." Like Barth, Mandela advances from a motive of reconciliation in the recollection of past horror. Though, for Mandela, humanity must "come to terms with the past" so that "we can bury those evil experiences" we must first remember. Recollection, however, is not for the sake of revenge or retribution, but for the goal of forgiveness, reconciliation, and ultimately blessed forgetting. Mandela and Barth thus share the conviction that by grace we may remember the past, through grace we can forgive time's evils, and in grace we might someday blessedly forget timeâ's horrors.